Science and Christianity in pulpit and pew - Numbers, Ronald L. (Oxford University Press, 2007)
Science and Christianity among the people : a vulgar history -- Science without God : natural laws and Christian beliefs -- Reading the book of nature through American lenses -- Experiencing evolution : psychological responses to the claims of science and religion -- Charles Hodge and the beauties and deformities of science -- "The most important biblical discovery of our time : William Henry Green and the demise of Ussher's chronology -- Science, secularization, and privatization : a concluding note